Isokinetic Effectiveness in Athletes After ACL Reconstruction Surgery: A Scope Review - Andara Gita Cahyani; Tyas Zhahro Amalia; Alya Zalfathia Kinanti; Nudya Fanizahra Nur Ramadhanti; Muchammad Yahya (Universitas Negeri Surabaya, 2025)
Background: Anterior cruciate ligament (ACL) injuries are a significant concern among athletes, often necessitating reconstructive surgery (ACLR) to restore knee function and enable return to sport. Objectives: This scope review aimed to evaluate the effectiveness of isokinetic exercise in the rehabilitation of athletes following ACLR, focusing on the optimal timing, training methods, and their impact on muscle strength and functional recovery. Methods: Articles published between 2016 and 2025 were systematically reviewed, with inclusion criteria emphasizing isokinetic interventions post-ACLR. Results: The analysis revealed that isokinetic training administered between 3 and 6 months post-ACLR significantly improves quadriceps and hamstring strength, enhances limb symmetry, and expedites knee function recovery. Isokinetic dynamometry at various angular velocities, combined with functional tests such as the Single-Leg Hop Test, was found to be effective in monitoring rehabilitation progress and determining readiness for return to sport. Conclusion: The findings underscore that well-timed and appropriately structured isokinetic exercise is an effective rehabilitation strategy for optimizing post-ACLR recovery in athletes, reducing muscle strength deficits, and minimizing the risk of re-injury..